A Neural Basis of Speech-in-Noise Perception in Older Adults - Anderson, Samira (2011)
OBJECTIVE: We investigated a neural basis of speech-in-noise perception in older adults. Hearing loss, the third most common chronic condition in older adults, is most often manifested by difficulty with understanding speech in background noise. This trouble with understanding speech in noise, which occurs even in individuals who have normal hearing thresholds, may arise, in part, from age-related declines in central auditory processing of the temporal and spectral components of speech. We hypothesized that older adults with poorer speech-in-noise (SIN) perception demonstrate impairments in the subcortical representation of speech. DESIGN: In all participants (28 adults, ages 60 to 73 years), average hearing thresholds calculated from 500 to 4000 Hz were ≤ 25 dB HL. The participants were evaluated behaviorally with the Hearing in Noise Test (HINT) and neurophysiologically using speech-evoked auditory brainstem responses recorded in quiet and in background noise. The participants were divided based on their HINT scores into top and bottom performing groups that were matched for audiometric thresholds and IQ. We compared brainstem responses in the two groups, specifically, the average spectral magnitudes of the neural response and the degree to which background noise affected response morphology. RESULTS: In the quiet condition, the bottom SIN group had reduced neural representation of the fundamental frequency of the speech stimulus and an overall reduction in response magnitude. In the noise condition, the bottom SIN group demonstrated greater effects of noise, which may reflect reduction in neural synchrony. All physiologic measures correlated with SIN perception. CONCLUSION: Adults in the bottom SIN group differed from the audiometrically-matched top SIN group in how speech was neurally encoded. The strength of subcortical encoding of the fundamental frequency appears to be a factor in successful speech-in-noise perception in older adults. Given the limitations of amplification for improving central auditory processing, our results indicate the need for inclusion of auditory training in intervention plans for older adults with SIN perception difficulties.